1987
DOI: 10.1007/bf00431013
|View full text |Cite
|
Sign up to set email alerts
|

A new mycotoxin from Aspergillus candidus Link isolated from rough rice

Abstract: A new mycotoxin (AcT1) was obtained from the mycelium of Aspergillus candidus Link isolated from rough rice stored under tropical conditions. AcT1 with the mol-formula C28H40O showed bright greenish blue fluorescence under uv (254 nm). The spectral and other characteristics indicated that the compound was a new one. The LD50 of the toxin on white rats was found to be 4.5 mg/Kg when injected intraperitoneally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In this work, A. candidus was detected under 18.5%/30°C. This mold is common in stored food grains (Chattopadhyay et al, 1987). Humidity is one of the crucial factors affecting the biodiversity and evolution of mold species during storage.…”
Section: Pcr-dgge Analysis Of Fungal Communitiesmentioning
confidence: 99%
“…In this work, A. candidus was detected under 18.5%/30°C. This mold is common in stored food grains (Chattopadhyay et al, 1987). Humidity is one of the crucial factors affecting the biodiversity and evolution of mold species during storage.…”
Section: Pcr-dgge Analysis Of Fungal Communitiesmentioning
confidence: 99%
“…Despite the frequent occurrence of this species the body of knowledge is considered as insufficient; it produces known metabolites, some of them showing cytotoxic activity: AcT1 (Chattopadhyay, Nandi et al 1987), xanthoascin (Ito, Ohtsubo et al 1978), terphenyllin (Marchelli and Vining 1975;Stead, Affleck et al 1999). However, there remains metabolites that are not yet identified and classified Andersen and Thrane 2006).…”
Section: Aspergillus Candidusmentioning
confidence: 99%
“…Earlier studies have reported this species to produce a variety of secondary metabolites (SM) such as patulin, pseurotin A and cytochalasin E (Zutz et al, 2013). On the other hand, other species which did not produce toxin in this study have been reported to be toxigenic in earlier studies for example; A. candidus was reported to produce a mycotoxin known as AcT1 (Chattopadhyay et al, 1987), whereas A. awamori has been reported to produce fumonisins (Storari et al, 2012) and aspochalamins A-D (Gebhardt et al, 2004). Aspergillus terreus has been reported to produce territrems in bakery products and grains (El-Sayed Abdalla et al, 1998).…”
Section: Discussionmentioning
confidence: 55%